Bridging adults and paediatrics with secondary hyperparathyroidism receiving haemodialysis: a pharmacokinetic‐pharmacodynamic analysis of cinacalcet. Issue 6 (25th April 2019) - Chen, Ping; Sohn, Winnie; Narayanan, Adimoolam; Gisleskog, Per Olsson; Melhem, Murad
Abstract : Aims: The aims of this study were to develop a pharmacokinetic (PK) and PK‐pharmacodynamic (PK/PD) model of cinacalcet in adults and paediatrics with secondary hyperparathyroidism (SHPT) on dialysis, to test covariates of interest, and to perform simulations to inform dosing in paediatrics with SHPT. Methods: Cinacalcet PK, intact parathyroid hormone (iPTH) and corrected calcium (cCa) time courses following multiple daily oral doses (1–300 mg) were modelled using a nonlinear mixed effects modelling approach using data from eight clinical studies. Model‐based trial simulations, using adult or paediatric titration schemas, predicted efficacy (iPTH change from baseline and proportion achieving iPTH decrease ≥30%) and safety (cCa change from baseline and proportion achieving cCa ≤8.4 mg/dL) endpoints at 24 weeks. Results: Cinacalcet PK parameters were described by a two‐compartment linear model with delayed first‐order absorption‐elimination (apparent clearance = 287.74 L h −1 ). Simulations suggested that paediatric starting doses (1, 2.5, 5, 10 and 15 mg) would provide PK exposures less than or similar to a 30 mg adult dose. The titrated dose simulations suggested that the mean (prediction interval) proportion of paediatric and adult subjects achieving ≥30% reduction in iPTH from baseline at Week 24 was 49% (36%, 62%), and 70.1% (62.5%, 77%), respectively. Additionally, the mean (confidence interval) proportion of paediatric and adult subjects achieving cCa ≤8.4 mg dL −1 at Week 24 was 8% (2%, 18%) and 23.6% (17.5%, 30.5%), respectively. Conclusions: Model‐based simulations showed that the paediatric cinacalcet starting dose (0.2 mg kg −1 ), titrated to effect, would provide the desired PD efficacy (PTH suppression <30%) while minimizing safety concerns (hypocalcaemia).